"Running is my boyfriend": consumers' relationships with activities. Issue 1 (13th February 2017) - Mickelsson, Karl-Jacob
Abstract : Purpose: The paper aims to introduce the idea that consumers have relationships with their own recurring activities. Instead of the usual notion of investigating the relationships between actors, or between actors and their possessions, the paper focuses on the relationship between an actor and a particular activity in which the actor regularly participates. Design/methodology/approach: The paper is conceptual and exploratory in nature. It discusses different perspectives of consumer activity in marketing and then introduces a relationship view of activity. The paper proceeds to outline the conceptual foundations of this view by applying relationship characteristics found in the literature. Quotes from runners' blogs are used to illustrate the different identified relationship themes. Findings: The paper argues that consumers can be seen as having long-term relationships with their activities, and it introduces the concept of the "activity relationship". The paper proceeds to demonstrate how this concept differs from the previous conceptualization of consumer activity and relationships. Research limitations/implications: The activity-relationship perspective on consumer behavior opens up new venues for marketing research. It also facilitates new types of marketing practice, whereby producers can focus on supporting their customers' relationships with valuable activities. Originality/value: The paper presents a novel perspective on relationships. It contributes to consumer research and the customer-dominant view of marketing, whereby the customer's perspective is put in focus and businesses serve as ingredients in the customer's own context.